The Effect of Village Nurse Performance on Community Satisfaction: Implications for Nursing Service Quality Management - Aprin Rusmawati; Alfian Fawzi; Intan Firasti Tamara; Agusta Dian Ellina; Mohamad Asad Efendy (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Community satisfaction is an important indicator in evaluating the quality of health services. One of the factors influencing satisfaction in village health services is the performance of village nurses who provide direct care through Posyandu activities. This study aimed to analyze the effect of village nurse performance on community satisfaction at Posyandu services in Tangkil Village. This study used a quantitative observational design with a cross-sectional approach. The population consisted of all Posyandu members in Tangkil Village, totaling 467 people. A sample of 215 respondents was selected using proportional random sampling. The independent variable was village nurse performance, while the dependent variable was community satisfaction level. Data were collected using structured questionnaires and analyzed using ordinal regression with a significance level of 0.05. The results showed that most respondents assessed village nurse performance as good (54.88%). Community satisfaction was also mostly categorized as very satisfied (54.88%). Statistical analysis indicated a significant effect of village nurse performance on community satisfaction (p = 0.000). In conclusion, better village nurse performance significantly increases community satisfaction in Posyandu services. Improving responsiveness, promotive efforts, preventive services, and communication skills is recommended to enhance public trust and participation in community health programs.